PELATIHAN RESIN MEJA KAYU UNTUK PENINGKATAN PERAN SERTA MASYARAKAT DALAM PENGEMBANGAN KEMITRAAN PARIWISATA DI KABUPATEN KAMPAR - Muchtar, Amrizal; Hanafi, Hanafi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Kampar Regency is an area that has the availability of natural wood products of 6,595,705 m and there is also a lot of this wood that is not used because of defects, but basically it can be creatively processed into handicraft and furniture products. The existence of this abundant wood became an inspiration for the Tourism and Culture Office of Kampar Regency, through the program in the Sub-Activity of Increasing Community Participation in Tourism Partnership Development for the 2021 Fiscal Year, which raised an activity with the theme "Training for Wood Table Resin". Resin wood table is one of the furniture products that is becoming a new trend among officials and people with upper middle economy in Riau province. Resin wood table offers a unique work of art and has a very luxurious and elegant aesthetic value, while providing an amazing prestige value for its owner. The purpose of the training is to assist youth in using resin and converting defective wood into products with high economic value. For this reason, the method used is the method of presentation, discussion, practice and demonstration and is accompanied by an active participation approach in training, so that it will be easier for participants to apply these skills properly. The results of the wood table resin training were carried out well and the outcome gave birth to new professionals in using resin in various wood furniture.